Enhancing Science Learning Outcomes Through The Course Review Horay (CRH) Cooperative Learning Model - Magfira, Siti; Sani, Nurul Kami; Zulnuraeni; Aras, Nurul Fitriah (Koordinat Jurnal MIPA, 2025)
This study aims to determine the learning outcomes of students taught using the Course Review Horay (CRH) cooperative learning model in the IPAS subject (Ilmu Pengetahuan Alam dan Sosial, translated as Integrated Science and Social Studies) for fifth-grade students at SD Inpres 2 Talise, a public elementary school in Palu, Indonesia. A quantitative approach was applied using a pre-experimental design, specifically the one-group pretest-posttest design. The population consisted of all fifth-grade students from classes V A and V B in the 2024/2025 academic year, totaling 34 students. The sample included 20 students from class V A, selected through random sampling. Data were collected using learning outcome tests, observation sheets, and interviews. Data analysis involved both descriptive and inferential statistics. The results showed an increase in the average score from the pretest (38.85) to the posttest (54.70). Statistical analysis using SPSS version 27 revealed a significant value of sig (2-tailed) = 0.001, which is less than 0.05. This indicates that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, suggesting that the Course Review Horay (CRH) model significantly influences the improvement of students’ learning outcomes in IPAS. These findings support the use of cooperative learning models, particularly CRH, as an effective strategy to enhance student engagement and achievement in primary school science education